Usada Taru Premana (Jahe merah) dan Akupresur Tingkatkan Immunitas di Masa Pandemi Covid-19 - Sang Ayu Ketut Candrawati; Ni Komang Sukraandini; Ni Kadek Yuni Lestasi; Ni Ketut Citrawati (Jurnal Akademika Baiturrahim Jambi, 2021)
The world including Indonesia was shocked by a new outbreak named coronavirus disease 2019 (Covid-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The spread of the Covid-19 virus is very fast, in Indonesia Covid-19 cases in March 2021 reached 430,458 cases with the number of deaths due to Covid-19 as many as 38,753 cases. Various efforts have been made by the government in order to suppress and break the chain of transmission of Covid-19, including involving educational institutions, both government and private. The government's appeal is to maintain body immunity during the pandemic to prevent the spread of the Covid-19 virus. One way to keep immunity stable is by utilizing natural elements such as the use of medicinal plants and also utilizing the body's energy in maintaining immunity as one of the promotive and preventive efforts. One of the therapies that is popular among the public is herbal therapy or traditional therapy called usadha taru premana therapy where red ginger is believed to have properties to maintain good immunity. Herbal therapy will have a good level of effectiveness when combined with modern therapies such as complementary therapies, one of which is acupressure. Acupressure is a massage therapy by pressing the body's meridian points which are believed to increase the immunity of the human body. Purpose: The review literature aim to see the effectiveness of Usada Taru Premana Combination of Acupressure as an alternative therapy to increase Immunity during the Covid-19 Pandemic Period. Methods: The method used in this literature review is to review articles using the Prisma method and quasi-experimental research design, analytical descriptive, literature review, survey and case reports based on evidence. Inclusion criteria were all studies reviewed in the form of research related to usadha taru premana red ginger; acupressure and immunity. Results: The number of journals reviewed for this study was 7, from 2017 to 2021. Conclusion: Based on a review conducted by researchers, it was found that red ginger and acupressure were effective for increasing immunity during the Covid-19 pandemic